Experimental study of motor cycle performance with exhaust manifold using torque expansion chamber - Subroto Subroto; Sartono Putro; Pramuko Ilmu Purboputro (JTTM : Jurnal Terapan Teknik Mesin, 2024)
The Motorcycle performance can be improved by modifying the intake manifold and exhaust manifold. In this research, the exhaust manifold was modified using a Torque Expansion Chamber (TEC), namely adding a tube to the exhaust manifold with a certain geometry and dimensions so that the heat carried by the exhaust gas is retained and does not directly escape through the exhaust. This test aims to determine the performance of a motorbike with a modified exhaust manifold by adding 250 mm tubular TEC. TEC installation with placement at 40%, 50%, and 60% of the exhaust manifold length. Engine performance including torque, power and specific fuel consumption is measured using the Dyno Test. The research results show that the use of the Torque Expansion Chamber has an effect on motorbike performance. Highest torque with 50% TEC placement and 60% TEC placement at 5000 rpm. Highest power with 50% TEC placement and 60% TEC placement at 6000 rpm to 6500 rpm. Lowest specific fuel consumption with 50% TEC placement at 6000 rpm